Case report: A novel 5'-UTR-exon1-intron1 deletion in MLYCD in an IVF child with malonyl coenzyme A decarboxylase deficiency and literature review - Xu, Fang; Wu, Yangyang; Huang, Jiyi; Zhou, Yunguo; Xu, Fei; Duan, Junkai; Li, Hong (Frontiers in Medicine, 2023)
A 11-months old IVF baby girl with the typical clinical manifestation of malonyl coenzyme A decarboxylase deficiency comprising developmental delay, limb weakness, cardiomyopathy, and excessive excretion of malonic acid and methylmalonic acid was studied in this report. Whole genome sequencing (WGS) revealed that a novel heterozygous nonsense mutation (c.672delG, p.Trp224Ter) in the proband and her father and a novel heterozygous deletion comprising 5’-UTR-exon1-intron1 in the proband and her mother. The patient’s cardiac function and limb weakness improved considerably after 3 months of feeding with low-fat diet supplemented with L-carnitine.